Self-management in Heart Failure: The Importance of Self-regulation but not Complexity of Condition. (April 2022) - Zaharova, Svetlana; Litwack, Kim; Gopalakrishnan, Sandeep; Ellis, Julie; Saltzberg, Mitchell Todd
Heart failure (HF) is a growing public health problem. Self-management (SM) of HF is an important component of chronic disease management. Guided by the Individual and Family Self-Management Theory (IFSMT), we examined the associations among complexity of condition, self-regulation, and self-efficacy mediation of SM behaviors in a population of HF outpatients. A cross-sectional design was used. Seventy-three outpatients with HF were enrolled. Simple and multiple linear regressions were run for each outcome variable. Only self-regulation was significantly associated with SM behavior. Complexity of condition was not significantly associated with SM behavior. There was no mediation by self-efficacy. Future nursing interventions should explore self-regulation in HF to provide a clearer understanding of the processes used to change health behavior. SM may be particularly useful in HF with preserved ejection fraction (EF), where there is no proven pharmacological treatment.